2011
DOI: 10.1002/smll.201101719
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Pillared Graphene‐Paper Electrodes for High‐Performance Electrochemical Supercapacitors

Abstract: Flexible graphene paper (GP) pillared by carbon black (CB) nanoparticles using a simple vacuum filtration method is developed as a high-performance electrode material for supercapacitors. Through the introduction of CB nanoparticles as spacers, the self-restacking of graphene sheets during the filtration process is mitigated to a great extent. The pillared GP-based supercapacitors exhibit excellent electrochemical performances and cyclic stabilities compared with GP without the addition of CB nanoparticles. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
196
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(204 citation statements)
references
References 44 publications
5
196
2
1
Order By: Relevance
“…The rGO-PPy60 paper presented a maximum energy density of 61.3 μWh cm -2 at a power density of 1.2 mW cm -2 , while it maintained 49.5 μWh cm -2 at 14.2 mW cm -2 . Our rGO-PPy paper displayed higher energy density compared to the reported results for graphene paper [10], graphenepolypyrrole film [23], graphene-PANI paper [52], or even graphene-MnO 2 electrode [41] especially at high power density.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The rGO-PPy60 paper presented a maximum energy density of 61.3 μWh cm -2 at a power density of 1.2 mW cm -2 , while it maintained 49.5 μWh cm -2 at 14.2 mW cm -2 . Our rGO-PPy paper displayed higher energy density compared to the reported results for graphene paper [10], graphenepolypyrrole film [23], graphene-PANI paper [52], or even graphene-MnO 2 electrode [41] especially at high power density.…”
Section: Resultsmentioning
confidence: 59%
“…Although these graphene-based flexible electrodes present promising gravimetric capacitance, they normally deliver a very low areal capacitance in the range of 57 to 94.5 mF cm -2 due to the low areal mass loading (< 1 mg cm -2 ) [9,10]. For practical usage, it is suggested that the areal mass loading is at least 5 mg cm -2 and the electrode thickness is between 50-200 μm [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene films can be prepared through various methods including vacuum filtration [94][95][96], drop-casting [97,98], layer-by-layer assembly [99] and through the compression of graphene aerogel or graphene foam [100,101]. However, the electrochemical performance of graphene films is restricted by the restacking of graphene sheets, because agglomeration decreases the specific surface area and results in more difficult diffusion of the electrolyte ions.…”
Section: Graphene Filmsmentioning
confidence: 99%
“…Spacers used include surfactants, polymers, nanoparticles and even water. [15][16][17][18] The approaches used to construct threedimensional porous graphene assembly involve the technique of hydrothermal, 19 template-assisted CVD, organic sol-gel 20,21 and freeze drying.…”
Section: Introductionmentioning
confidence: 99%